2019
DOI: 10.3390/ijms20184420
|View full text |Cite
|
Sign up to set email alerts
|

miR-34a-5p Increases Hepatic Triglycerides and Total Cholesterol Levels by Regulating ACSL1 Protein Expression in Laying Hens

Abstract: Accumulating evidence has shown that miR-34a serves as a posttranscriptional regulatory molecule of lipid metabolism in mammals. However, little studies about miR-34a on lipid metabolism in poultry have been reported until now. To gain insight into the biological functions and action mechanisms of miR-34a on hepatic lipid metabolism in poultry, we firstly investigated the expression pattern of miR-34a-5p, a member of miR-34a family, in liver of chicken, and determined its function in hepatocyte lipid metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…With the start of laying, a sharp raised EBP-like expression level in liver was observed from pre-laying stage (20 weeks old) to peak-laying hens (30 weeks old). A same rising trend of cholesterol levels was previously found in laying hens ( Tian et al, 2019 ). The present results were consistent with previous studies and further supported our hypothesis that EBP-like playing the same role in cholesterol biosynthesis in chickens.…”
Section: Discussionsupporting
confidence: 86%
“…With the start of laying, a sharp raised EBP-like expression level in liver was observed from pre-laying stage (20 weeks old) to peak-laying hens (30 weeks old). A same rising trend of cholesterol levels was previously found in laying hens ( Tian et al, 2019 ). The present results were consistent with previous studies and further supported our hypothesis that EBP-like playing the same role in cholesterol biosynthesis in chickens.…”
Section: Discussionsupporting
confidence: 86%
“…The knockdown of miR-34a can inhibit lipid accumulation and reduce liver cell steatosis [64]. In chicken liver, miR-34a-5p promotes the accumulation of TG by regulating the expression of long-chain acyl-CoA synthetase 1 (ACSL1), and it has a function similar to that of human and mouse hepatocytes, thus achieving the positive regulation of fatty acid synthesis [65]. Interestingly, miR-221-5p was highly conserved among species including mammals, and gga-miR-221-5p was involved in liver lipid metabolism; our study results may also provide a valuable reference for humans in lipid study.…”
Section: Discussionmentioning
confidence: 99%
“…Long-chain acyl-CoA synthetase (ACSL) is a candidate gene for the regulation of skeletal muscle fatty acid composition [ 15 ] and catalyzes the conversion of long-chain fatty acids into acyl-CoA [ 46 ]. ACSL1 as a dominating family member, is involved in multiple lipid metabolism pathways, including biosynthesis of unsaturated fatty acids, PPAR signaling, and fatty acid metabolism pathways [ 14 ].…”
Section: Important Genes Involved In Chicken Fat Metabolismmentioning
confidence: 99%
“…MiR-34a-5p, a member of the miR-34a family, is responsible for increasing the intracellular levels of TG, as well as total cholesterol in hepatocytes by inhibiting the translation of its target gene, ACSL1, in chicken livers. It is indicated that miR-34a-5p has a significantly higher expression level in the liver of peak laying hens compared with prelaying hens and closely related to lipid metabolism [ 46 ]. Besides, the differential expression analysis of miRNAs in Gushi chicken breast muscle at different development stages showed that miR-34a-3p is a stage-specific miRNA that was abundantly expressed at 30 weeks of chicken age [ 15 ].…”
Section: Chicken Mirnasmentioning
confidence: 99%